Buku Cerita Bergambar Tentang Legenda Kisah Joko Bodo Untuk Anak-Anak Sebagai Media Edukasi - Lely Surya Wardani; Muhammad Haris Sulton (University of Nahdlatul Ulama Pasuruan, 2025)
Mount Budeg is an educational tourist destination that holds a legendary story passed down from generation to generation. However, the rapid development of digital technology has caused this story to begin fading away, reducing the bond between parents and children, and weakening children's moral values toward their parents. To address this issue, a picture storybook was created that embeds moral messages to shape children’s character. This research uses a qualitative method, starting with direct observation at Mount Budeg, interviews with local caretakers and cultural experts to explore the mountain’s history, interviews with children to understand their attitudes and character, and a literature study to enrich the content with valid sources. The book design process began with gathering references, followed by creating thumbnails and rough layouts, and finally, completing the book digitally. The book was delivering moral messages, increasing reading interest, and introducing folklore to children in an enjoyable way. It can be concluded that this picture storybook has successfully become an educational medium that not only entertains but also shapes children's character and helps preserve local cultural values.